HUBUNGAN ANTARA FREKUENSI PEMBERIAN TABLET DENGAN PENINGKATAN HEMOGLOBIN PADA IBU HAMIL: KAJIAN SISTEMATIS DAN META-ANALISIS - Anggita Putri Samara; Festi Artika Sari; Della Anastasia Candra; Muhammad Ja'far Shodiq; Adil Jihad Muhammad; Arfina Prihatini; Atika Atika (E-Jurnal Medika Udayana, 2021)
Background: The prevalence of anemia in pregnant women in the world is still high. WHO recommends consuming iron tablets of 60-120 mg/day. But, there are side effects such as nausea and vomiting, which cause low levels of adherence. Iron supplements may be consumed daily or weekly. Objective: to analyze the significance of the effect of the frequency of iron tablet administration on increasing hemoglobin levels in pregnant women. Methods: This study used an observational analytic design with a systematic review method based on several randomized controlled trials. The research literature search criteria used the PICO method. The results of the correlation between the increase in hemoglobin levels before and after giving iron tablets daily or weekly in pregnant women were summarized based on the p-value, Standard Mean Difference, meta regression, and 95% CI (confidence interval) which were used to evaluate the results of the relationship between the frequency of giving iron tablets with increased hemoglobin levels in pregnant women. The data was processed with Review Manager software ver 5.4.1. Results: This study uses a collection of research with searches on google scholar, science direct and pubmed. There were 8 studies that were selected. Statistical analysis obtained Standard Mean Difference 0.28 (0.06-0.49) with 95% CI (p <0.05) and meta regression was performed on daily and weekly administration with p value 0.15. Conclusion: There was no significant difference between the frequency of daily and weekly administration (p> 0.05). However, the increase in hemoglobin on the daily administration was more significant than the weekly one. Keywords : Iron supplementation, Pregnant women, Frequency.